The Effect of Handgrip Exercises on Blood Pressure (Global Journal of Medical Research, 2020)
Background: Hypertension is a major risk factor that contributes to cardiovascular disease, including coronary artery disease, stroke, and heart failure. Aim of the study: That handgrip exercises may also be effective for a ssisting with blood pressure management and adjust ability of a low-intensity working. Methods: Twenty high normal and prehypertensive indiv iduals without pharmacological, aged between 50and 65 years, males and Females, conducted with handgrip exercises for 8 weeks. Participant's performed 4#xD7;2 minute isometric handgrip exercises with their non-dominant hand, each separated by a 3-minute rest period, 3 days a week. Results: Blood pressure measurements were conducted at baseline and at the end of the protocol using a wrist blood pressure monitor. Eight weeks of isometric resistance training resulted in a 7-mmHg reduction of resting systolic blood pressure (SBP) (136#xB1;12 to 129#xB1;15); (P=0.04). Reductions of 4mmHg were also seen in mean arterial pressure (MAP) (100#xB1;8to96#xB1;11);( P=0.04).
Keywords: hypertension; handgrip exercises